TPGS-STABILIZED RESVERATROL NANOSUSPENSION ENHANCES FUNCTIONAL RECOVERY IN A MOUSE MODEL OF SCIATIC NERVE INJURY - Zahid Sarfraz; Shumaila Kiran; Sarosh Iqbal; Kanwal Rehman; Tahir Farooq (Journal of Animal and Plant Sciences, 2026)
The low solubility and bioavailability issues of natural compounds challenge their applications and the wide spectrum of bioactivities. Recently, great efforts have been made to develop nanoformulations of bioactive compounds to enhance their efficacy profiles. They increase their bioavailability through a targeted, controlled and sustained release for a prolonged period. Naturally occurring resveratrol (Res), is a highly active nonflavonoid polyphenol, showing several bioactivities including anticancer, antioxidant, antidiabetic and anti-inflammatory potential. In this study, the nanosuspensions (NS) of Res were prepared with and without D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as a stabilizing agent. Further, the prepared NS1 (Res only) and NS2 (TPGS + Res) were administered through daily gavage (20mg/mL) to accelerate functional recovery and regeneration following peripheral nerve injury (PNI) in a mouse model. A total of eighteen mice were used, equally divided (six/group) into three groups: a control and two treatment groups under a completely randomized design (CRD). The NS-mediated regain of sensory functions was evaluated by a hot plate test in NS-treated and control animals. Furthermore, the recovery of motor function was examined employing the sciatic functional index and muscle grip strength studies. Nerve regeneration highly depends on oxidative stress and blood glycemic level. Therefore, the total antioxidant capacity (TAC), total oxidant status (TOS) and blood glucose were also assessed in NS-treated groups compared to the control. The prepared NS2 induced the maximum hypoglycemic effects, resulting in a controlled glucose level and regulation of oxidants with a significantly improved TAC. These improved biochemical attributes provided a growth-permissive environment, facilitating the nerve regeneration and functional recovery after PNI owing to the enhanced bioavailability of Res.
Keywords: Drug delivery system; antioxidant; controlled release; entrapped drug